Carbonic anhydrase II as host protein for the creation of a biocompatible artificial metathesase. Issue 20 (20th April 2015) - Zhao, Jingming; Kajetanowicz, Anna; Ward, Thomas R.
Abstract : We report an efficient artificial metathesase which combines an arylsulfonamide anchor within the protein scaffold human carbonic anhydrase II. Abstract : An artificial metathesase results from incorporation of an Hoveyda-Grubbs catalyst bearing an arylsulfonamide anchor within human carbonic anhydrase II. The optimization of the catalytic performance is achieved upon combining both chemical and genetic means. Up to 28 TONs were obtained within four hours under aerobic physiological conditions.